Analysis of morphometric data for drainage basins in Hafr Al Batin city, northeast of Saudi Arabia using GIS - Al-Buhaithi, Nawaf bin Hamed (Journal of natural sciences, life and applied sciences, 2020)
This study provides a geomorphological analysis of the properties of the valleys of the city of Hafr al-Batin using Geographic information systems (GIS) techniques that helped extract the parametric properties and the matrix properties used in the application of the SCS dimensionless Unit hydrograph to calculate the flow Peak of each valley. The results of the application of this model have shown that Seoul's studied valleys flow during periods varying from one water basin to another between 4.38 hours in the basin (1) F 26.44 hour in the tub (9) and at a size between 30.00 M 3/sec (1) F 257.58 M 3/sec in pelvis (10), and at speeds of between 1.50 m/sec (2) F (5 (f 2.37 m/sec in Basin (9)). The spatial analysis outputs of ARC GIS also assisted in the extraction of 12 morphological variables and 11 variable scales, which helped to classify studied streams by every variable.
Keywords: morphometric data; drainage basins; geographic information systems; Hafar Al-Batin